Company Size And Debt To Equity Ratio To Corporate Bond Yield To Maturity: Ukuran Perusahaan Dan Debt To Equity Ratio Terhadap Yield To Maturity Obligasi Korporasi - Ramadhan, Zulfikar; Sutanti; Munawaroh, Azizatul; Oktariani, Dwi (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to determine the effect of firm size and debt to equity ratio on the yield to maturity of corporate bonds. The research design is associative with quantitative type. The data used is secondary data in the form of financial reports published by the Indonesia Stock Exchange. The population used is all sectoral companies that issue corporate bonds for the 2017-2020 period listed on the Indonesia Stock Exchange and the Indonesia Central Securities Depository so that the selected population is 109 companies. The sampling technique uses the purposive samplingmethod, so that the selected sample is 4 companies. The analytical method used is multiple linear regression. By doing the classical assumption test, regression equation analysis, and the feasibility test of the regression model in which it is known that firm size has a positive and significant effect on the yield to maturity of corporate bonds, in addition the debt to equity ratio has positive and significant effect. To the yield to maturity of corporate bonds.